Pelvic Organ Prolapse Stage and the Relationship to Genital Hiatus and Perineal Body Measurements - Dunivan, Gena C (Female Pelvic Med Reconstr Surg, 2016)
OBJECTIVES: Describe the relationship between genital hiatus (GH) and perineal body (PB) measurements with increasing pelvic organ prolapse stage in a large cohort of women referred to Urogynecology clinic for pelvic floor disorders. METHODS: Retrospective chart review of all new patients seen in an academic Urogynecology clinic between 1/2007 and 9/2011. Data were extracted from a standardized intake form. All patients underwent a Pelvic Organ Prolapse Quantification (POPQ) exam. Descriptive statistics compared the study population. Analysis of variance (ANOVA) was used to compare GH and PB measurements by prolapse stage. Fishers least significant differences was used for post hoc comparisons of means between prolapse stages. Pearson's correlations were used to evaluate the associations between GH and PB measurements and patient characteristics. RESULTS: 1595 women with POPQ exams comprised the study population. The mean age was 55.3 ±14.8 years with a BMI 30.3 ± 7.6 kg/m2, most women were parous (90%), 40% were Hispanic, 33% had undergone prior hysterectomy for indications exclusive of pelvic organ prolapse. Woman with any prior prolapse repair were excluded, 6.5% had a prior incontinence procedure. PB measurements were slightly larger for Stage 2 pelvic organ prolapse (POP), but overall did not vary across other prolapse stages (all P >0.05). In contrast, GH measurements increased through stage 3 POP, GH measurements decreased for stage 4 POP. CONCLUSIONS: Mean PB measurements did not demonstrate large changes over prolapse stage, while GH measurements increased through stage 3 POP. GH serves as an important marker for underlying pelvic muscle damage.